The many faces of philosophy - Amélie Oksenberg Rorty (Oxford University Press, 2003)
This historically based collection of philosophers' reflections--the letters, journals, prefaces that reveal their hopes and hesitations, their triumphs and struggles, their deepest doubts and convictions--allow us to witness philosophical thought-in-process. It sheds light on the many--and conflicting--aims of philosophy: to express skepticism or overcome it, to support theology or attack it, to develop an ethical system or reduce it to practical politics. As their audiences differed, philosophers experimented with distinctive rhetorical strategies, writing dialogues, meditations, treatises, aphorisms